Application of droplet motion and phase change model in containment spray system. (September 2019) - Zhao, Fulong; Yan, Xiao; Bo, Hanliang; Meng, Tao; Zeng, Chen; Tan, Sichao
Highlights: The multi-droplets motion and phase change model was formulated. The present model was utilized to simulate droplet spraying in the containment. The parameters of the containment were presented against experimental results. Influence of spray droplet parameters on the system performance was analyzed. Abstract: The containment spray system is a vital part of the nuclear power plant to reduce the temperature and pressure within the containment during a hypothetical severe accident, which is bound up with the safety of the nuclear reactor. To investigate the performance of the containment spray system, the model coupling the multi-droplets motion and phase change model inducing the local gas parameters surrounding the droplets is formulated. The proposed model is utilized to simulate the droplet spraying process in the containment. The time evolution of various parameters of the containment spray system including the temperature, pressure, steam mass fraction, droplet sizes and trajectories were presented against the experimental results. Furthermore, the influence of the spray droplet parameters on the system performance was analyzed. The results indicate that the system performance is strongly dependent on the radii of the spray droplets, spray mass flow rate and the position distribution of the spraying nozzles, in the range of the temperature, pressure, droplet sizes, velocities and spray mass flow rate investigated. This study presents a droplet motion and phase change model that can be applied to droplet spray characteristics simulation, and performs a systematic analysis of the containment spray system performances. The results can be used to support the design and optimization of spray cooling systems in the containment and other applications.